Neutron Bragg edge imaging for strain characterization in powder bed additive manufacturing environments - Sumarli, Shieren (2022)
Spatially resolved studies of crystalline structures, e.g. lattice spacings, are enabled by recording the transmitted spectra in neutron Bragg edge imaging. The recorded signals are, however, a result of through-thickness averaging of the probed specimen in the beam direction. Therefore, it is challenging to extract the strain distribution when the strain varies across the thickness, which applies for studies on different materials or material states along the beam. Here we introduce the approach to disentangle contributions to the recorded signals, i.e. separating the transmission spectra of two different material states. This is particularly applicable to powder bed additive manufacturing environments where operando strain characterization of the printed specimen using neutrons is intended. In this work, Laser Powder Bed Fusion (PBF-LB/M)-built 316L and IN718 samples embedded in their corresponding powders are used, extracting the desired spectra of the printed specimen. The disentanglement is proven to be satisfactory by obtaining coinciding strain maps of identical specimens embedded in powder layers of different thicknesses. Furthermore, the obtained residual strain distributions of 316L samples were verified by conventional neutron diffraction with lower spatial resolution due to the gauge volume averaging.